Citizenship and social stratification - Coelho, Roseli Aparecida Martins (Universidade Estadual Paulista / UNESP, 2009)
Discursion on citizenship taken as "regulating idea". The possibility of applying the igualitarian ideal On the analysis of the underdeveloped capitalist societies. opposition between the "basic civil right" (right to work) and the necessities of the capitalist accumulation.